Comunicación en pareja y satisfacción marital“Unidad Educativa Vigotsky”. Riobamba, 2020. - Marcela María Soledad Fierro Villacreses (2021)
The satisfaction and the communication in everyday of the couple relationship life have a key role within the couple, so when one of these decreases it generates problems in the marital relationship, this research aimed to analyze couple communication and marital satisfaction in the parents of the Vigotsky Educational institution, it was a study with a quantitative approach of a bibliographic and field type, with a cross-sectional design, and with a descriptive research level, the study had a sample of 100 parents who were evaluated with two psychological instruments: the Marital Communication Scale (COMARI) designed by the psychologist Nina Ruth Estrella in 1991 and the Marital Satisfaction Inventory Revised (MSI-R), created by Ph.D Douglas K. Snyder in 1981, the results in terms of marital communication show that couples speak little about children 51%, marital relationship 59%, extended family 65%, sexual life 59%, feelings, emotions and dislikes 65%, work 50%;regarding marital satisfaction, a moderate level is indicated on the 54% inconsistency scales, conventionalism 36%, global anxiety 67%, aggression 42%, role orientation 53%, family history of anxiety 39% and conflicts over raising children 47%. Due to the results obtained has been elaborated a psychoeducational plan that is oriented to improve the communication and marital satisfaction of the parents of the institution.